Inhibiting Adipose Tissue Lipogenesis Reprograms Thermogenesis and PPARγ Activation to Decrease Diet-induced Obesity - Lodhi, Irfan J. (2012)
De novo lipogenesis in adipocytes, especially with high fat feeding, is poorly understood. We demonstrate that an adipocyte lipogenic pathway encompassing fatty acid synthase (FAS) and PexRAP (Peroxisomal Reductase Activating PPARγ) modulates endogenous PPARγ activation and adiposity. Mice lacking FAS in adult adipose tissue manifested increased energy expenditure, increased brown fat-like adipocytes in subcutaneous adipose tissue, and resistance to diet-induced obesity. FAS knockdown in embryonic fibroblasts decreased PPARγ transcriptional activity and adipogenesis. FAS-dependent alkyl ether phosphatidylcholine species were associated with PPARγ and treatment of 3T3-L1 cells with one such ether lipid increased PPARγ transcriptional activity. PexRAP, a protein required for alkyl ether lipid synthesis, was associated with peroxisomes and induced during adipogenesis. PexRAP knockdown in cells decreased PPARγ transcriptional activity and adipogenesis. PexRAP knockdown in mice decreased expression of PPARγ–dependent genes and reduced diet-induced adiposity. These findings suggest that inhibiting PexRAP or related lipogenic enzymes could treat obesity and diabetes.